Socioeconomic indicators, obesity, and physical fitness in south Brazilian adolescents with Down syndrome. (20th October 2018) - Izquierdo-Gomez, Rocio; Marques, Alexandre
Abstract : Objectives : The aim was to examine the association of potential socioeconomic indicators with obesity and physical fitness components in south Brazilian adolescents with Down syndrome. Methods : This study comprised a total of 1249 (669 boys) adolescents with Down syndrome aged 10 to 20 with complete baseline data. Socioeconomic indicators were assessed by a proxy-report questionnaire. Body mass index and physical fitness were assessed using a PROES-BR health-related fitness test battery. Results : Socioeconomic status is not associated with body mass index in adolescents with Down syndrome. In addition, two of five physical fitness variables were associated with groups of family income and paternal education level in boys, while one of five physical fitness variables were associated with groups of paternal and maternal education level in girls. Conclusion : Our results suggest that socioeconomic indicators are associated with some components of physical fitness in Brazilian adolescents with Down syndrome. These associations depend on the socioeconomic status and physical fitness components in boys and girls.